A novel approach of using transtibial transport (TTT) to manage thromboembolic events following surgical management of necrotizing soft tissue infection: a case report - Boey, Johnson; Lee, Jordon; Zhou, ZheGang (Frontiers in Medicine, 2025)
Necrotising soft tissue infections (NSTIs) are one of the most challenging and severe forms of infections. The prognosis requires accurate and aggressive diagnosis and management. In this case, we present an unexplained case of concurrence of TE events following BKA for the surgical management of NSTI. As with the standard management, the first step involves aggressive surgical debridement of non-viable tissue which eventually lead to below-knee amputation for effective source control. Lower limb endovascular angioplasty was attempted but unsuccessful. The PAD was managed with antithrombotic therapy. In spite of this, the patient developed thromboembolic events 1 week following BKA. In response, the antiplatelet therapy with low-molecular weight heparin was enhanced. Transtibial transport was performed after patient found to have stenosis in distal tibial arteries, which the patient refused any further vascular intervention. Nonetheless, with meticulous planning and concerted team efforts, we successfully reversed TE events and salvaged the contralateral limb without the need for amputation. With intensive rehabilitation, the patient was able to return to their pre-morbid functional quality of life.